2019
DOI: 10.3928/24748307-20190325-01
|View full text |Cite
|
Sign up to set email alerts
|

The Impact and Outcomes of Integrating Health Literacy Education Into Adult Basic Education Programs in Boston

Abstract: Background:Adult basic education (ABE) is the national system that offers educational services in English language development, reading, writing, math, technology, and communications to adults with low literacy, limited English, or both. These services range from basic levels to high school equivalency, with specialty programs in transition to community colleges and family literacy.Objective:This study sought to analyze the role of ABE in increasing health literacy among low literate and limited English popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…We developed a peer language navigator (PLN) program. In concept, this program has some similarities to the approachs described by Hohn (1997), Spener (1992), and others (Bishop, Earp, Eng, & Lynch, 2002; Chervin, Clift, Woods, Krause, & Lee, 2012; Elder, 2003; Findley, & Matos, 2015; Garner, 2008; Schecter, & Lynch, 2011; Soto Mas, Mein, Fuentes, Thatcher, & Balcázar, 2013; Wright, & Grabowsky, 2011) for providing health education to people with low literacy. The program is based at the Alaska Literacy Program (ALP), which is where new immigrants and refugees in Anchorage go to learn English.…”
Section: Program Implementationmentioning
confidence: 95%
“…We developed a peer language navigator (PLN) program. In concept, this program has some similarities to the approachs described by Hohn (1997), Spener (1992), and others (Bishop, Earp, Eng, & Lynch, 2002; Chervin, Clift, Woods, Krause, & Lee, 2012; Elder, 2003; Findley, & Matos, 2015; Garner, 2008; Schecter, & Lynch, 2011; Soto Mas, Mein, Fuentes, Thatcher, & Balcázar, 2013; Wright, & Grabowsky, 2011) for providing health education to people with low literacy. The program is based at the Alaska Literacy Program (ALP), which is where new immigrants and refugees in Anchorage go to learn English.…”
Section: Program Implementationmentioning
confidence: 95%
“…Research studies about the impact and outcomes of integrating health found that ABE programs are a good place to learn about health, and are particularly effective when coordinated with local health services. Learners have been highly receptive to learning about health in ABE classrooms (Hohn, 1998; Levy et al, 2008; Rivera & Hohn, 2010).…”
Section: History Of Adult Basic Education and Health Care Efforts To mentioning
confidence: 99%
“…Low levels of health literacy are associated with an inefficient use of preventive healthcare services, an increased number of hospital visits, increased healthcare costs and deterioration of public health [7]. In line with these requirements, as in all other fields, in order to live a better life and maximize the health literacy of individuals, various health education projects are being developed under the title of adult education and health literacy education [8].…”
Section: Introductionmentioning
confidence: 99%